Lysine and Polyamines Are Substrates for Transglutamination of Rho by the Bordetella Dermonecrotic Toxin - Schmidt, Gudula (American Society for Microbiology, 2001)
Bordetella dermonecrotic toxin (DNT) catalyzes the transglutamination of glutamine-63/61 of Rho GTPases, thereby constitutively activating Rho proteins. Here we identified second substrates for transglutamination of RhoA by DNT. The enzymatically active fragment of DNT (residues 1136 to 1451, ΔDNT) induced the incorporation of l-[(14)C]lysine in RhoA in a concentration-dependent manner. Also, Rac and Cdc42, but not Ras, were transglutaminated with lysine by ΔDNT. Transglutamination of the GTPase with l-lysine inhibited intrinsic and Rho-GAP-stimulated GTP hydrolysis of RhoA. In contrast to lysine, treatment of RhoA with alanine, arginine, and glutamine were not able to substitute for lysine in the transglutamination reaction. DNT increased the incorporation of l-[(14)C]lysine into embryonic bovine lung cells. Microinjection of GST-RhoA together with the enzymatically active DNT fragment into Xenopus oocytes, subsequent affinity purification of modified GST-RhoA, and mass spectrometry identified attachment of putrescine or spermidine at glutamine-63 of RhoA. A comparison of putrescine, spermidine, and lysine as substrates for DNT-induced transglutamination of RhoA revealed that lysine is a preferred second substrate at least in vitro.